ANALISIS KINERJA IFRS X PURWOKERTO DARI PERSPEKTIF PERTUMBUHAN DAN PEMBELAJARAN BALANCED SCORECARD - Fithria Dyah Ayu Suryanegara; Achmad Fudholi; Satibi Satibi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
IFRS X is an integral part of the hospital, and has a strategic role in the professional development of hospitals and hospital economics. IFRS X in order to enter the business environment in the future an increasingly competitive, requiring the measurement of performance in order to survive and compete. Therefore, the performance measured in terms of IFRS X from the perspective of growth and learning balanced scorecard. Methods in cross-sectional study was conducted, and data collected in the form of quantitative data obtained by observation and dissemination of data questionnaire. The results showed that from the perspective of growth and learning, the performance of IFRS X has shown good results, judging from the 80.77% level of employee satisfaction, employee productivity levels 93.59% and 42.31% level of employee training.